Policy entrepreneurship and the influence of the transnational financial industry in the EU reform of securitization. (March 2020) - Montalbano, Giuseppe
Abstract: According to most of the literature available so far, international and European cross-border banks and investments firms are considered the primary beneficiaries of the CMU and related revitalization of securitization. Nevertheless, an in-depth analysis of the transnational financial industry lobbying and influence, in the light of the final agreement on the securitization reform package, is still missing. This paper intends to fill this gap in the story by assessing if, and to what extent, the alleged industry beneficiaries played an active role in shaping the regulatory agenda within the CMU project and its related outcomes. An in-depth analysis of corporate lobbying in the securitization reform is thus provided, by looking at the interactions between structural and political contextual factors in shaping private/public coalitions along the different stages of the EU policy-making process. As it is argued here, the policy entrepreneurship of the European securitization industry has been the key factor to explain the emergence of the EU regulatory approach and its legislative outcomes.